New subclasses of univalent functions and their properties / Yuzaimi Yunus - Yunus, Yuzaimi (2023)
In this thesis, the boundaries of knowledge on geometric function theory is extended with the discovery of interesting new subclasses of univalent functions plus their properties. The main theme of this thesis is establishing these new classes to conform with existing geometric domains and ascertaining their properties using proven techniques. There are four different type of classes of functions introduced and their main properties studied.